2019
DOI: 10.1002/fsn3.1081
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Impact of drying methods on composition and functional properties of date powder procured from different cultivars

Abstract: The present study was designed to evaluate the effect of two different drying methods, that is, spray drying and oven drying on physicochemical and nutritional attributes of date flesh powder of dhakki, aseel, and rabi varieties. Date powders were prepared using mixture of maltodextrin and acacia gum (50:50) as drying aid at the rate of 0.4 kg per 1.0 kg of date fruits (dry weight basis). The oven‐drying conditions were 60°C for 48 hr, whereas in spray drying, flow rate of 30 ml/min at 150°C was maintained. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Our results are comparable with the findings of Moghbeli et al (2019) who reported moisture contents ranging from 1.48% to 3.45% for spray-dried date powders including pectinwhey protein complexes. Similar moisture contents were also reported by Raza et al (2019) for maltodextrin/gum arabic mixture-containing date powders obtained through ovendrying at 60°C (1.55-2.59%) and spray-drying (1.47-2.55%). On the other side, our findings are lower than those of Botrel et al (2016) (5.06-6.78%) who investigated the utilization of different ratios of inulin (20% or 30%) to produce araticum (Annona crassiflora) pulp powder using cabinet convective air dryer at 70, 80 or 90°C.…”
Section: Influence Of Inulin Amount On Physicochemical Characteristics Of Date Powderssupporting
confidence: 85%
See 3 more Smart Citations
“…Our results are comparable with the findings of Moghbeli et al (2019) who reported moisture contents ranging from 1.48% to 3.45% for spray-dried date powders including pectinwhey protein complexes. Similar moisture contents were also reported by Raza et al (2019) for maltodextrin/gum arabic mixture-containing date powders obtained through ovendrying at 60°C (1.55-2.59%) and spray-drying (1.47-2.55%). On the other side, our findings are lower than those of Botrel et al (2016) (5.06-6.78%) who investigated the utilization of different ratios of inulin (20% or 30%) to produce araticum (Annona crassiflora) pulp powder using cabinet convective air dryer at 70, 80 or 90°C.…”
Section: Influence Of Inulin Amount On Physicochemical Characteristics Of Date Powderssupporting
confidence: 85%
“…Inulin-containing date powders had ash contents of between 8.09% and 13.09% (Table 1). Comparatively low ash contents in date powders (4.73-5.76%) with maltodextrin/ gum arabic mixture were declared by Raza et al (2019). This remarkable difference may be the result of various drying-aid agent concentrations used in these studies and different accumulation of minerals in fruits due to cultivars, climate, growing location, and cultivation practices (organic/ conventional) (Boussaa et al, 2020;Kapoulas, Milenković and Mirecki, 2013;Marzouk and Kassem 2011).…”
Section: Influence Of Inulin Amount On Physicochemical Characteristics Of Date Powdersmentioning
confidence: 86%
See 2 more Smart Citations
“…Ash content remained unchanged during 90 days of storage time. Raza et al (2019) concluded that ash content of dried date powder procured from different cultivars remained unchanged after 2 months of storage period.…”
Section: Ash Content Of Date Barmentioning
confidence: 99%